Peran Biaya Pendidikan Dalam Memediasi Keputusan Orang Tua Siswa: Tinjauan pada Pemilihan SMK Swasta Pekanbaru - Rifzal, Rifzal; harwina, yulia (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This study aims to determine the effect of education costs on the parents' decision to choose SMK Swasta Pekanbaru. By using a total sample of 97 people. In this research, the writer uses incidental sampling research method using the SPSS method. From the results obtained tcount the variable cost of education is 10.229 and the value of ttable is 1.66105. So that tcount > ttable (10.229 > 1.66105) and a significant value of 0.000 <0.05, so it can be concluded that the education cost variable has a positive and significant effect on the parents' decisions. In testing the coefficient of determination (r2), the value of r = 0.524 means that the relationship between the independent variables (education costs) to the dependent variable (student parents' decisions) is 52.4%, which means that there is a close relationship. The value of r square = 0.524 means that the influence of the independent variable (education costs) on the dependent variable (student parents' decisions) is 34.2% and the remaining 47.6% is influenced by other variables that are not careful. Finally, from this study it can be concluded that the cost of education has a positive and significant influence on the decisions of parents, so it is advisable to choose SMK Swasta Pekanbaru to pay attention to the cost of education so that the parents' decisions are better to achieve the goal.